Absolute Environmental Sustainability Assessment of the Arid Central Asia by Downscaling Planetary Boundaries - Ziyang Zhu; Meiqing Feng; Yaning Chen; Weili Duan; Zhi Li; Wim Cornelis; Philippe DeMaeyer (Earth's Future, 2025)
Abstract Assessing absolute environmental sustainability (AES) is essential to ensure that human activities remain within a safe operating space. However, it remains unclear whether the planetary boundaries (PBs) have been breached in Central Asia. This study analyzed environmental pressures in arid Central Asia from 2000 to 2020 by downscaling PBs and evaluating AES ratios. Environmental distance was applied to identify environmental surpluses or overshoots, while an integrated environmental sustainability index (IESI) was to identify priority management areas. Domestic consumption dominated the environmental footprint during 2000–2020. Besides land footprint, water, carbon, nitrogen, phosphorus and human appropriation of net primary production to Central Asia were mainly from Europe and Asia. Kazakhstan and Uzbekistan were identified as IESI level III, becoming priority management areas for sustainable development. Improving resource utilization efficiency and strengthening trade cooperation can strengthen the PBs of arid Central Asia and promote sustainable environmental development.